Preventive Measures and Handling of COVID-19 and Emerging Disease in the Border Areas of West Kalimantan Province Entikong District and Jagoi Babang District - Saepudin, Malik; Pranaka, Resky Nanda; Baroroh, Ema Zati; Setyowati, Eny (Jurnal Penelitian Inovatif, 2024)
One of the country's entry points is the National Border Post (PLBN), which is the main key in preventing the entry of the COVID-19 pandemic into Indonesia because many people come and go from various places so that the country's entrance in border areas becomes one of the places at risk of spread. COVID-19 virus such as in Entikong District and Jagoi Babang District. This research was conducted to determine the description of knowledge, attitudes, prevention efforts, health service facilities and health promotions in the Entikong and Jagoi Babang border areas, determine the influence of prevention efforts on the incidence of COVID-19, determine the influence of health service facilities and health promotions on the incidence of COVID-19 and find out the reality of implementing 3T. This research uses a mix method research design, namely a research step that combines two forms of research approaches, namely qualitative and quantitative. The sampling technique used purposive sampling with a total of 156 respondents who were divided into two groups, namely the case group and the control group. The following is a description of the research results, namely: 1) The case group in the Entikong border area has the highest presentation of low knowledge, poor attitude presentation, poor presentation of prevention efforts, and poor health facility presentation compared to the Jagoi Babang border area and the two regions combined, 2 ) There is a significant influence in efforts to prevent the incidence of COVID - 19, 3) There is a significant influence of health service facilities and health promotions in preventing the incidence of COVID - 19, 4) There are factors that encourage and hinder someone from carrying out a COVID - 19 test in the area borders, 5) There are obstacles in implementing the handling of COVID - 19 in border areas, and 6) There are problems in implementing handling of COVID - 19 in border areas..